НУРТАЙ БАТЫР - Тилеўмуратов, М. (ILIM hám JÁMIYET, 2017)
The article is devoted to the description of the struggle of the Karakalpak people’s hero Nurtay-the son of Jangeldi-batir for the freedom of people in the XVIII-th century on the basis of historical documents of the Karakalpaks of the New river and the work «Genealogy» by Berdakh. The author of the article comes to the conclusion that Nurtay-batir Jungeldi-uli was the hero and leader of the people’s struggle for freedom and national independence in the XVIII-th century.